2008
DOI: 10.1051/0004-6361:20079192
|View full text |Cite
|
Sign up to set email alerts
|

Heating the corona by nanoflares: simulations of energy release triggered by a kink instability

Abstract: Context. The heating of solar coronal plasma to millions of degrees is likely to be due to the superposition of many small energyreleasing events, known as nanoflares. Nanoflares dissipate magnetic energy through magnetic reconnection. Aims. A model has been recently proposed in which nanoflare-like heating naturally arises, with a sequence of dissipation events of various magnitudes. It is proposed that heating is triggered by the onset of ideal instability, with energy release occurring in the nonlinear phas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
144
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 104 publications
(160 citation statements)
references
References 33 publications
(49 reference statements)
15
144
1
Order By: Relevance
“…The helical deformation of the kink instability generates current sheets in the nonlinear regime, in which fast magnetic reconnection rapidly dissipates magnetic energy. Recently, it has been demonstrated using 3D MHD simulations that this process causes the field to relax towards a state which is closely-approximated as a constant-α state, and the energy release is in good agreement with relaxation theory (Browning et al 2008;Hood et al 2009). These papers have investigated field profiles, based on the model of Browning & Van der Linden (2003), in the unstable region of parameter space and have shown that fast reconnection develops in a current sheet, with dissipation of magnetic energy and relaxation to a new, lower-energy state.…”
Section: Introductionsupporting
confidence: 54%
See 3 more Smart Citations
“…The helical deformation of the kink instability generates current sheets in the nonlinear regime, in which fast magnetic reconnection rapidly dissipates magnetic energy. Recently, it has been demonstrated using 3D MHD simulations that this process causes the field to relax towards a state which is closely-approximated as a constant-α state, and the energy release is in good agreement with relaxation theory (Browning et al 2008;Hood et al 2009). These papers have investigated field profiles, based on the model of Browning & Van der Linden (2003), in the unstable region of parameter space and have shown that fast reconnection develops in a current sheet, with dissipation of magnetic energy and relaxation to a new, lower-energy state.…”
Section: Introductionsupporting
confidence: 54%
“…This is unrealistic in the context of the solar corona; the loop would be more stable than it might be otherwise. Browning et al (2008) plotted the relationship between the growth rate of the instability and the distance to the outer surface of the potential envelope (i.e., a more distant conducting wall). They found that for six unstable loop states the growth rate was invariant once the outer surface of the envelope (R 3 ) exceeded 3 2 R 2 .…”
Section: Equilibrium Fieldsmentioning
confidence: 99%
See 2 more Smart Citations
“…When the two speeds are equal, the ions and electrons are about to separate, and this will lead to the higher (anomalous) resistivities associated with collisionless reconnection. For an ionized hydrogen plasma, Z = 1 and m i = m p , and, since the plasma is still (although only just) a single fluid, T e = T. Equation (3.11) therefore simplifies to 12) which can expressed in code normalized units, 13) through the use of the appropriate normalizing constants,…”
Section: (B) Critical Current Densitymentioning
confidence: 99%